Hot melt adhesive and preparation method thereof

Through the addition of specific combinations of polyolefin elastomers and amorphous plastics, as well as modified particles and amorphous plastics APAO, the problem of insufficient adhesion and mechanical properties of hot melt adhesives to difficult-to-adhesive substrates is solved. It has achieved multi-performance improvement of hot melt adhesive and is suitable for the automotive field.

CN118909567BActive Publication Date: 2025-02-11KEJIAN POLYMER MATERIALS (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411407206.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-11
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing hot melt adhesives have insufficient adhesion and mechanical properties to difficult-to-adhesive substrates such as PP/PE in the automotive field, and are not well resistant to aging, corrosion resistance and waterproof and moisture resistance, which cannot meet the performance of hot melt adhesives in the automotive industry. diversity needs.

Method used

Using specific combinations of polyolefin elastomers and amorphous plastics, the mechanical properties and cohesion of hot melt adhesives are improved by forming physical crosslinking points and enhancing the degree of molecular chain entanglement. At the same time, modified particles and amorphous plastic APAO are added to enhance the intermolecular adhesion effect and particle connection strength, and a multi-level barrier structure is formed to improve waterproof and moisture resistance.

Benefits of technology

It has achieved good adhesion and mechanical properties of hot melt adhesive to difficult-to-adhesive substrates such as PP/PE, and maintained excellent aging resistance, corrosion resistance and waterproofing and moisture resistance, meeting the diversity of hot melt adhesive properties of the automotive industry need.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of hot melt adhesives, and in particular to a hot melt adhesive and a preparation method thereof. A hot melt adhesive, in parts by mass, comprises raw materials including: 5 to 12 parts of polyolefin elastomer, 40 to 60 parts of amorphous plastomer, 25 to 40 parts of tackifying resin, 10 to 20 parts of modified particles, 1 to 3 parts of antioxidant, 5 to 15 parts of lubricant, 1 to 5 parts of softener, 1 to 4 parts of cross-linking agent, and 1 to 2 parts of initiator. The hot melt adhesive prepared in the present application not only has good adhesion and mechanical properties for difficult-to-bond substrates such as PP / PE, but also can maintain its own excellent aging resistance, corrosion resistance, and waterproof and moisture resistance, meeting the existing automotive industry application requirements for the performance diversity of hot melt adhesives, and has very excellent application prospects in the automotive field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hot melt adhesives, and in particular to a hot melt adhesive and a preparation method thereof. Background Art

[0002] In automotive applications, hot melt adhesives are widely used due to their fast curing, good bonding properties, and ability to adapt to a variety of substrates. These adhesives are usually applied at high temperatures and form a strong bond once cooled. Their applications in automotive manufacturing include, but are not limited to, fixing interior trims, body sealing, and bonding shock and sound insulation materials.

[0003] As the automotive industry's demand for lightweight, environmental protection and cost-effectiveness increases, the research and development of hot melt adhesives also tends to meet higher performance standards. For example, the market has given higher requirements for the bonding performance of hot melt adhesives. When existing hot melt adhesives are used for bonding car roofs, they have good bonding effects on steel plates, galvanized plates, ASB / PC, glass fibers, films and silk fabrics, but have poor bonding effects on difficult-to-bond substrates such as PP / PE, and their mechanical properties, aging corrosion resistance, and waterproof and moisture resistance are obviously insufficient.

[0004] Therefore, in order to make up for the deficiencies of the above-mentioned prior art, the present application provides a hot melt adhesive and a preparation method. The hot melt adhesive prepared in the present application not only has good adhesion and mechanical properties for difficult-to-bond substrates such as PP / PE, but also can maintain its own excellent aging resistance, corrosion resistance, and waterproof and moisture resistance, which meets the performance diversity requirements of the existing automotive industry for hot melt adhesives and has very excellent application prospects in the automotive field. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides a hot melt adhesive, which includes, by mass, 5 to 12 parts of polyolefin elastomer, 40 to 60 parts of amorphous plastic, 25 to 40 parts of tackifying resin, 10 to 20 parts of modified particles, 1 to 3 parts of antioxidant, 5 to 15 parts of lubricant, 1 to 5 parts of softener, 1 to 4 parts of cross-linking agent, and 1 to 2 parts of initiator.

[0006] As a preferred solution, the mass ratio of the polyolefin elastomer, the amorphous plastic and the tackifying resin is (6-10): (45-58): (25-35).

[0007] As a preferred solution, the mass ratio of the polyolefin elastomer, the amorphous plastic and the tackifying resin is (7-8): (45-54): (26-35).

[0008] As a preferred solution, the mass ratio of the amorphous plastic to the modified particles is (45-58): (12-18).

[0009] As a preferred solution, the mass ratio of the amorphous plastic to the modified particles is (45-54):(14-16).

[0010] As a preferred solution, the polyolefin elastomer is an ethylene-α-olefin copolymer.

[0011] As a preferred solution, the Mooney viscosity ML1+4 of the polyolefin elastomer at 121° C. is 30-40MU.

[0012] As a preferred solution, the Mooney viscosity of the ethylene-α-olefin copolymer is 32-35MU, ML1+4, 121°C.

[0013] As a preferred solution, the amorphous plasticizer is an amorphous α-olefin copolymer APAO.

[0014] As a preferred solution, the weight average molecular weight of the amorphous plastic is 70,000-100,000 Da.

[0015] As a preferred solution, the weight average molecular weight of the amorphous α-olefin copolymer APAO is 80,000-90,000 Da.

[0016] The combination of the above-mentioned specific polyolefin elastomer and amorphous plasticizer added in the present application can effectively improve the adhesion of the hot melt adhesive to difficult-to-bond substrates, and help improve its mechanical, waterproof and aging corrosion resistance. The combined addition of polyolefin elastomer and amorphous plasticizer can effectively utilize the long-chain branching structure in the polyolefin elastomer to form physical cross-linking points, enhance the degree of entanglement between the amorphous plasticizer and its molecular chain, and thus greatly enhance the density of the cross-linking network inside the hot melt adhesive. In addition, due to the insertion of the polyolefin elastomer molecular chain, the mechanical properties of the hot melt adhesive can be effectively improved through the good retraction of its molecular chain. The presence of the branched structure can also effectively limit the molecular chain slippage of the amorphous plasticizer, thereby obtaining good cohesion of the hot melt adhesive system. On the other hand, the addition of the amorphous plasticizer APAO can enhance the strong intermolecular interactions it contains. It can specifically enhance the intermolecular adhesion effect on PP / PE substrates and enhance specific adhesion. The low molecular weight molecular chain segment of APAO can effectively reduce the overall melt viscosity of the hot melt adhesive, and the amorphous region can serve as a soft segment region to reduce the glass transition temperature and enhance flexibility and viscosity. Finally, it can also form a good active connection with the modified composite structure particles, greatly enhancing the connection strength and number of molecular chains in the micropores of the modified particles, increasing the force dissipation effect and water molecule barrier effect of the particle micropores, thereby maintaining excellent mechanical, waterproof and aging and corrosion resistance properties under long-term use and in specific environments.

[0017] As a preferred solution, the tackifying resin is at least one of hydrogenated hydrocarbon resin, terpene resin, C5 petroleum resin, C9 petroleum resin, phenolic resin, and styrene-conjugated diene block copolymer.

[0018] As a preferred solution, the tackifying resin is a hydrogenated hydrocarbon resin.

[0019] As a preferred solution, the softening point of the hydrogenated hydrocarbon resin is 110-130°C.

[0020] As a preferred solution, the modified particles are modified composite structure particles; the preparation method of the modified composite structure particles comprises the following steps: S1: adding sericite powder to deionized water, adding ammonia water to adjust the pH to 10-10.5, then adding tetraethyl orthosilicate, triethanolamine and isopropanol, heating to 60-65°C, rotating at 60-80 rpm, stirring for 1.5-2h, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated sericite powder; S2: adding the pretreated sericite powder to deionized water, then adding glutaric anhydride and titanate coupling agent, heat to 60~65℃, rotate at 60~80rpm, stir and react for 2~3h to obtain modified sericite powder; S3: add modified sericite powder, aluminum nitrate, terephthalic acid and acetic acid to deionized water and stir evenly at room temperature, then add into a closed reactor, control the reactor pressure at 2.1~2.4MPa, gradually heat to 200~220℃ at a heating rate of 2~3℃ / min, stir and react at 120~160rpm for 14~20h, release the pressure after the reaction is completed, and naturally cool to room temperature and wash and filter with methanol, and vacuum dry to obtain.

[0021] As a preferred solution, the mass ratio of the sericite powder, tetraethyl orthosilicate, triethanolamine and isopropyl alcohol is (5-5.5): (0.8-1): (0.3-0.4): (0.1-0.2).

[0022] As a preferred solution, the mass ratio of the pretreated sericite powder, glutaric anhydride and titanate coupling agent is (3-3.4): (1-1.2): (0.15-0.2).

[0023] As a preferred solution, the mass ratio of the modified sericite powder, aluminum nitrate, terephthalic acid and acetic acid is (2-2.5): (0.8-1): (1-1.2): (10-15).

[0024] As a preferred solution, the titanate coupling agent is tetraisopropoxy titanate.

[0025] As a preferred solution, the average particle size of the sericite powder is 1-2 μm.

[0026] The modified composite structure particles prepared by the above method in the present application can greatly improve the mechanical properties, aging corrosion resistance, water resistance and moisture resistance of the hot melt adhesive, and can effectively maintain the bonding performance of the hot melt adhesive. In the present application, the surface of the flaky particles of sericite powder is preferentially coated with amorphous silica, and then the surface groups of the surface silica layer after curing are modified, so as to form a good mosaic surface matrix in the subsequent synthesis of framework particles. When the framework particles are formed, they can be stably loaded on the flaky sericite particles to form a point-modified flaky composite structure. The existence of this structure can utilize the good spreading effect of the flaky sericite substrate in the hot melt adhesive system, as well as the active connection between the modified surface groups and the hot melt adhesive system, to greatly improve the connection force between the modified composite structure particles and the hot melt adhesive resin system. It can not only greatly improve the modified particles through the heat flow carrier effect of the amorphous plastic The modified particles not only have uniform dispersion and fixed properties after curing, but also can provide excellent support and connection effects when the hot melt adhesive is subjected to external forces through connecting forces and point-surface supporting effects after curing. On the other hand, the spread modified particles can form a good trapezoidal barrier structure in the sol system. The existence of this multi-level structure can greatly improve the barrier effect of the hot melt adhesive system for water molecules and free groups, greatly increase the resistance to the penetration of water molecules and active molecules, reduce the aggregation and freeness of active molecules, water molecules and other molecules with water molecules as carriers, thereby avoiding the probability of active reactions inside the hot melt adhesive, and maintaining good waterproof, moisture-resistant, aging-resistant and corrosion-resistant properties during long-term use.

[0027] As a preferred solution, the antioxidant is any one of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant 1098, and antioxidant 1024.

[0028] As a preferred solution, the antioxidant is antioxidant 1010.

[0029] As a preferred solution, the lubricant is at least one of polyethylene wax, polypropylene wax, microcrystalline wax, zinc stearate, calcium stearate, and stearic acid amide.

[0030] As a preferred solution, the lubricant is polyethylene wax.

[0031] As a preferred solution, the softener is at least one of white oil, epoxidized soybean oil, naphthenic oil, polyisobutylene, and polyethylene glycol.

[0032] As a preferred solution, the softener is white oil or epoxidized soybean oil.

[0033] As a preferred solution, the crosslinking agent is at least one of maleic anhydride, dimethyl maleate, diethyl maleate, N-phenylmaleimide, N-cyclohexylmaleimide, glycidyl ether type epoxy resin, hexamethylene diisocyanate, and vinyl trimethoxysilane.

[0034] As a preferred solution, the cross-linking agent includes maleic anhydride and dimethyl maleate.

[0035] As a preferred solution, the mass ratio of maleic anhydride to dimethyl maleate is (4.5-5):(1.2-2).

[0036] As a preferred solution, the initiator is any one of peroxide initiators.

[0037] As a preferred solution, the initiator is dicumyl peroxide.

[0038] The second aspect of the present application provides a method for preparing the above-mentioned hot melt adhesive, which specifically comprises the following steps: (1): mixing a tackifying resin, an antioxidant, a lubricant and a softener, heating the mixture to 140-150°C, and stirring and mixing at 100-120 rpm to obtain a mixture; (2): placing the mixture in a vacuum high-speed mixer, adding a polyolefin elastomer and an amorphous plasticizer, heating the mixture to 160-180°C, and stirring and mixing at 300-400 rpm for 2-2.5 hours to obtain a hot melt adhesive base material; (3): transferring the hot melt adhesive base material to an extruder, adding modified particles, a cross-linking agent and an initiator, heating at 140-160°C for 1-1.5 hours, and then melt-extruding and granulating to obtain the hot melt adhesive base material.

[0039] The beneficial effects of this application are:

[0040] 1. A hot melt adhesive provided in the present application not only has good adhesion and mechanical properties for difficult-to-bond substrates such as PP / PE, but also can maintain its own excellent aging resistance, corrosion resistance, waterproof and moisture resistance, meeting the performance diversity requirements of the existing automotive industry for hot melt adhesives, and has very excellent application prospects in the automotive field.

[0041] 2. A hot melt adhesive provided in the present application, the combination of a specific polyolefin elastomer and an amorphous plasticizer added thereto can effectively utilize the long-chain branched structure in the polyolefin elastomer to form physical cross-linking points, enhance the entanglement between the amorphous plasticizer and its molecular chain, and thereby greatly enhance the density of the cross-linked network inside the hot melt adhesive. In addition, due to the insertion of the polyolefin elastomer molecular chain, the mechanical properties of the hot melt adhesive can be effectively improved through the good retractability of its molecular chain. The presence of the branched structure can also effectively limit the molecular chain slippage of the amorphous plasticizer, thereby obtaining good cohesion of the hot melt adhesive system.

[0042] 3. A hot melt adhesive provided in the present application, the addition of the amorphous plastic APAO can enhance the strong intermolecular interaction contained therein, specifically enhance the intermolecular adhesion effect on the PP / PE substrate, enhance the specific adhesion, and the low molecular weight molecular chain segment of APAO can effectively reduce the overall melt viscosity of the hot melt adhesive, the amorphous region can serve as a soft segment region, reduce the glass transition temperature, and enhance flexibility and viscosity; finally, it can also form a good active connection with the modified composite structure particles, greatly enhance the molecular chain connection strength and number in the modified particle micropores, increase the force dissipation effect and water molecule barrier effect of the particle micropores, and thus maintain excellent mechanical, waterproof and aging and corrosion resistance properties under long-term use and in specific environments.

[0043] 4. A hot melt adhesive provided in the present application comprises modified particles added by preferentially coating the surface of flaky particles of sericite powder with amorphous silica, and then modifying the surface groups of the surface silica layer after curing, thereby forming a good mosaic surface matrix in the subsequent synthesis of framework particles. When the framework particles are formed, they can be stably loaded on the flaky sericite particles to form a point-modified flaky composite structure. The existence of this structure can utilize the good spreading effect of the flaky sericite substrate in the hot melt adhesive system, as well as the active connection between the modified surface groups and the hot melt adhesive system, to greatly improve the connection force between the modified composite structure particles and the hot melt adhesive resin system. Not only can the dispersion uniformity of the modified particles and the fixation of the particles after curing be greatly improved through the heat flow carrier effect of the amorphous plastic, but also after curing, through the connection force and point-surface support effect, it can provide excellent support and connection effects when the hot melt adhesive is subjected to external forces.

[0044] 5. A hot melt adhesive provided in the present application, the added modified particles can form a good trapezoidal barrier structure in the sol system. The existence of the multi-level structure can greatly improve the barrier effect of the hot melt adhesive system for water molecules and free groups, greatly increase the resistance to the penetration of water molecules and active molecules, reduce the aggregation and free phenomenon of active molecules, water molecules and other molecules with water molecules as carriers, thereby avoiding the probability of active reactions inside the hot melt adhesive, and maintaining good waterproof, moisture-resistant, aging-resistant and corrosion-resistant properties during long-term use. DETAILED DESCRIPTION

[0045] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0046] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0047] Example 1

[0048] The first aspect of Example 1 provides a hot melt adhesive, in which the raw materials include, by mass: 7 parts of polyolefin elastomer, 50 parts of amorphous plastic, 30 parts of tackifying resin, 15.5 parts of modified particles, 1 part of antioxidant, 7 parts of lubricant, 2 parts of softener, 2 parts of cross-linking agent, and 1 part of initiator.

[0049] The polyolefin elastomer is an ethylene-α-olefin copolymer with a Mooney viscosity of 33MU, ML1+4, and 121° C. It is purchased from the Dow Chemical Company of the United States and is a product of model ENGAGE 8150.

[0050] The amorphous plastomer is an amorphous α-olefin copolymer APAO with a weight average molecular weight of 85,000 Da, and is purchased from Evonik of Germany as a product of model Vestoplast 891.

[0051] The tackifying resin is a hydrogenated hydrocarbon resin having a softening point of 115° C. and is purchased from Eastotac H130W sold by Eastman.

[0052] The modified particles are modified composite structure particles; the preparation method of the modified composite structure particles comprises the following steps, measured in parts by mass: S1: adding 5.4 parts of sericite powder to 200 parts of deionized water, adding ammonia water to adjust the pH to 10.2, then adding 0.95 parts of ethyl orthosilicate, 0.32 parts of triethanolamine and 0.16 parts of isopropanol, heating to 62°C and stirring at 80 rpm for 2 hours, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated sericite powder; S2: adding 3.3 parts of pretreated sericite powder to 160 parts of deionized water, then adding 1.1 parts of glutaric acid anhydride and 0.18 parts of titanate coupling agent, heat to 65℃, rotate at 80rpm, stir and react for 3h to obtain modified sericite powder; S3: add 2.2 parts of modified sericite powder, 0.85 parts of aluminum nitrate, 1.1 parts of terephthalic acid and 14 parts of acetic acid to 220 parts of deionized water, stir evenly at room temperature, then add to a closed reactor, control the pressure of the reactor to 2.3MPa, gradually heat to 210℃ at a heating rate of 2.5℃ / min, stir and react at 140rpm for 18h, release the pressure after the reaction is completed, and naturally cool to room temperature and wash and filter with methanol, and vacuum dry to obtain.

[0053] The titanate coupling agent is tetraisopropoxy titanate; and the average particle size of the sericite powder is 1.6 μm.

[0054] The antioxidant was antioxidant 1010; the lubricant was polyethylene wax purchased from Westlake Chemical under the model EPOLENE E-43 WAX.

[0055] The softener was white oil, which was purchased from Shandong Zhengxin Energy Technology Co., Ltd. and sold as white oil No. 10.

[0056] The crosslinking agent is a composition of maleic anhydride and dimethyl maleate, and the mass ratio of the two is 4.6:1.4; the initiator is diisopropylbenzene peroxide.

[0057] The second aspect of the present embodiment provides a method for preparing the above-mentioned hot melt adhesive, which specifically includes the following steps: (1): Mix a tackifying resin, an antioxidant, a lubricant and a softener, heat to 145°C, and stir and mix evenly at 110rpm to obtain a mixture; (2): Place the mixture in a vacuum high-speed mixer, add a polyolefin elastomer and an amorphous plasticizer, heat to 180°C, and stir and mix at 400rpm for 2.5h to obtain a hot melt adhesive base material; (3): Transfer the hot melt adhesive base material to an extruder, add modified particles, a cross-linking agent and an initiator, heat at 150°C for 1.5h, and then melt-extrude and granulate to obtain the hot melt adhesive base material.

[0058] Example 2

[0059] The specific implementation of Example 2 is basically the same as that of Example 1, with the only difference being that: the hot melt adhesive, in parts by mass, comprises the following raw materials: 7 parts of polyolefin elastomer, 54 parts of amorphous plastic, 26 parts of tackifying resin, 12.2 parts of modified particles, 1 part of antioxidant, 8 parts of lubricant, 2 parts of softener, 2 parts of cross-linking agent, and 1 part of initiator.

[0060] Example 3

[0061] The specific implementation of Example 3 is basically the same as that of Example 1, with the only difference being that: the raw materials of the hot melt adhesive, in parts by mass, include: 7 parts of polyolefin elastomer, 45 parts of amorphous plastic, 35 parts of tackifying resin, 17.5 parts of modified particles, 1 part of antioxidant, 6 parts of lubricant, 2 parts of softener, 2 parts of cross-linking agent, and 1 part of initiator.

[0062] Comparative Example 1

[0063] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that: the raw materials of the hot melt adhesive, in parts by mass, include: 7 parts of polyolefin elastomer, 50 parts of amorphous plasticizer, 30 parts of tackifying resin, 7.5 parts of modified particles, 1 part of antioxidant, 12 parts of lubricant, 2 parts of softener, 1 part of cross-linking agent, and 1 part of initiator.

[0064] Comparative Example 2

[0065] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that: the raw materials of the hot melt adhesive, in parts by mass, include: 20 parts of polyolefin elastomer, 35 parts of amorphous plasticizer, 20 parts of tackifying resin, 16.5 parts of modified particles, 1 part of antioxidant, 8 parts of lubricant, 2 parts of softener, 2 parts of cross-linking agent, and 1 part of initiator.

[0066] Comparative Example 3

[0067] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that: the raw materials of the hot melt adhesive, in parts by mass, include: 3.5 parts of polyolefin elastomer, 70 parts of amorphous plasticizer, 15 parts of tackifying resin, 15.5 parts of modified particles, 1 part of antioxidant, 7 parts of lubricant, 2 parts of softener, 2 parts of cross-linking agent, and 1 part of initiator.

[0068] Comparative Example 4

[0069] The specific implementation of this comparative example is basically the same as that of Example 1, except that the amorphous plastomer is an amorphous α-olefin copolymer APAO with a weight average molecular weight of 55,000 Da, which is purchased from Evonik of Germany.

[0070] Comparative Example 5

[0071] The specific implementation of this comparative example is basically the same as that of Example 1, except that the polyolefin elastomer is an ethylene-α-olefin copolymer with a Mooney viscosity of 22MU, ML1+4, 121°C, and is purchased from the Dow Chemical Company of the United States as an ENGAGE 8440 product.

[0072] Comparative Example 6

[0073] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified composite structure particles comprises the following steps, calculated by mass: S1: adding 9.5 parts of sericite powder to 240 parts of deionized water, adding ammonia water to adjust the pH to 10.2, then adding 0.65 parts of ethyl orthosilicate, 0.2 parts of triethanolamine and 0.1 parts of isopropanol, heating to 62°C and stirring at 80 rpm for 2 hours, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated sericite powder; S2: adding 5.5 parts of pretreated sericite powder to 160 parts of deionized water, then adding 0. .8 parts of glutaric anhydride and 0.12 parts of titanate coupling agent, heat to 65℃, rotate at 80rpm, stir and react for 3h to obtain modified sericite powder; S3: add 2.2 parts of modified sericite powder, 0.85 parts of aluminum nitrate, 1.1 parts of terephthalic acid and 14 parts of acetic acid to 220 parts of deionized water, stir evenly at room temperature, then add to a closed reactor, control the pressure of the reactor to 2.3MPa, gradually heat to 210℃ at a heating rate of 2.5℃ / min, stir at 140rpm and keep warm for 18h, release the pressure after the reaction is completed, and naturally cool to room temperature and wash and filter with methanol, and vacuum dry to obtain.

[0074] Comparative Example 7

[0075] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified composite structure particles comprises the following steps, calculated by mass: S1: adding 5.4 parts of sericite powder to 200 parts of deionized water, adding ammonia water to adjust the pH to 10.2, then adding 0.95 parts of ethyl orthosilicate, 0.32 parts of triethanolamine and 0.16 parts of isopropanol, heating to 62°C and stirring at 80 rpm for 2 hours, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated sericite powder; S2: adding 3.3 parts of pretreated sericite powder to 160 parts of deionized water, then adding Add 1.1 parts of glutaric anhydride and 0.18 parts of titanate coupling agent, heat to 65°C and stir at 80rpm for 3h to obtain modified sericite powder; S3: add 4.5 parts of modified sericite powder, 0.65 parts of aluminum nitrate, 0.8 parts of terephthalic acid and 5 parts of acetic acid to 240 parts of deionized water and stir evenly at room temperature, then add to a closed reactor, control the pressure of the reactor to 2.3MPa, gradually heat to 210°C at a heating rate of 2.5°C / min, stir at 140rpm and keep warm for 18h, release the pressure after the reaction is completed, and naturally cool to room temperature and wash and filter with methanol, and vacuum dry to obtain.

[0076] Comparative Example 8

[0077] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of the sericite powder is 4.5 μm.

[0078] Performance Evaluation

[0079] Softening point test: Take appropriate amount of sample and prepare sample. Test with ring and globe softening point tester.

[0080] Hot melt stability test: Put 2 / 3 of hot melt adhesive in a 100ml crucible and test it in a 197℃ oven for 72h to observe whether there is gel, skinning, or delamination. If there is no gel, skinning, or delamination, the test is passed; if there is any of the following phenomena, the test is failed.

[0081] Peel test: melt the sample in an oven at 170°C, press it into a 1mm thick specimen, cut a 100mm×25mm specimen after cooling, place it on an aluminum foil (0.1mm) of 250mm×25mm, and then melt it in an oven at 170°C. Immediately paste PP / PE of 150mm×25mm, roll it back and forth 3 times with a 2kg roller, cool it to room temperature, trim the sample that overflows from the edge, run 3 cycles under the conditions of (40°C, 95%RH) for 24h, (23°C, 50%RH) for 1h, 85°C, 24h, (23°C, 50%RH) for 1h, -30°C, 4h, (23°C, 50%RH) for 1h, take it out and let it stand for 24h before testing.

[0082] Shear strength test: According to ISO 4587-2 standard, the shear strength of the sample is tested. After the sample is melted in a 170℃ oven, it is pressed into a 1mm thick specimen. After cooling, a 12.5mm×25mm specimen is cut and placed on a 100mm×25mm aluminum foil (0.1mm). After melting in a 170℃ oven, it is immediately pasted with a 100mm×25mm PP / PE substrate, rolled back and forth 3 times with a 2kg roller, and then placed under standard conditions for 3 days before testing.

[0083] Static load test: melt the sample in a 170℃ oven, press it into a 1mm thick specimen, cut a 25mm×25mm specimen after cooling, and paste it on a 25mm×25mm×1mm aluminum sheet. Place the middle section of a 400mm×0.05mm nylon wire horizontally in the center of the aluminum sheet, melt it in a 170℃ oven, and immediately paste it on a 100mm×100mm×1mm PP plate. After cooling to room temperature, cut off the sample overflowing from the edge, hang a 200g weight on the thin wire, and observe it in a 110℃ oven for 24 hours. The passing condition is: the weight does not fall off after 24 hours.

[0084] Opening hours: HG / T3716-2003 test standard.

[0085] Aging resistance test: After curing the hot melt adhesive prepared in the embodiment and the comparative example, a 2cm×2cm×0.2cm sample was prepared, and placed in a constant temperature and humidity chamber at 68±2°C and 75±3% relative humidity, and stored for 6 months. After 6 months, record whether the sample has yellowing, oxidation, cracking, blistering and damage. If so, it is recorded as unqualified, otherwise it is qualified. 50 samples were tested in each group to record the qualified rate of the samples, and the results are recorded in Table 2.

[0086] Waterproof test: After curing the hot melt adhesive prepared in the embodiment and the comparative example, a 2cm×2cm×0.2cm sample was prepared. The surface water contact angle was tested by the sessile drop method. The test water droplet was 2.5μL and the test time was 60s. The water contact angle of the hot melt adhesive surface at 60s was recorded. The test value was the average of 10 tests and recorded in Table 2.

[0087] Corrosion resistance: After the hot melt adhesives prepared in the examples and comparative examples were cured, samples of 2 cm × 2 cm × 0.2 cm were prepared for salt spray resistance test. The test environment temperature was 35 ± 2 ° C, the humidity was 95 ± 2%, the test solution was 5wt% NaCl solution, the spray angle was 25 °, the spray rate was 2mL / 80 cm² / h, and the test time was 400h. After the test, the cured hot melt adhesive was observed for corrosion, shedding, cracking and blistering. If there were any, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group to record the qualified rate of the samples, and the results were recorded in Table 2.

[0088]

[0089]

[0090] It can be seen from the examples and comparative examples of the present application and the data results in Tables 1 to 2 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 8 in terms of bonding performance, hot melt stability, mechanical properties, aging corrosion resistance and other aspects. This is mainly due to the combined effect of the specific functional resins, modified particles and other matching schemes specified in the present application. Comparative examples 1 to 8 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A hot melt adhesive, characterized in that: The raw materials include, by weight: 5-12 parts of polyolefin elastomer, 40-60 parts of amorphous plastomer, 25-40 parts of tackifying resin, 10-20 parts of modified particles, 1-3 parts of antioxidant, 5-15 parts of lubricant, 1-5 parts of softener, 1-4 parts of crosslinking agent, and 1-2 parts of initiator; The Mooney viscosity ML1+4 of the polyolefin elastomer at 121° C. is 30-40MU; The weight average molecular weight of the amorphous plastic is 70000-100000Da; The tackifying resin is at least one of hydrogenated hydrocarbon resin, terpene resin, C5 petroleum resin, C9 petroleum resin, phenolic resin, and styrene-conjugated diene block copolymer; The modified particles are modified composite structure particles; the preparation method of the modified composite structure particles comprises the following steps: S1: adding sericite powder to deionized water, adding ammonia water to adjust the pH to 10-10.5, then adding tetraethyl orthosilicate, triethanolamine and isopropanol, heating to 60-65°C, rotating at 60-80rpm, stirring for 1.5-2h, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated sericite powder; S2: adding the pretreated sericite powder to deionized water, then adding glutaric anhydride and titanate coupling agent, heating to 60-65°C, rotating at 60-80rpm, stirring for 1.5-2h ... centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated sericite powder; The mixture was heated to 60-65°C and stirred at 60-80 rpm for 2-3 hours to obtain modified sericite powder; S3: the modified sericite powder, aluminum nitrate, terephthalic acid and acetic acid were added to the deionized water and stirred evenly at room temperature, and then added to a closed reactor, the pressure of the reactor was controlled to be 2.1-2.4 MPa, and the temperature was gradually increased to 200-220°C at a heating rate of 2-3°C / min, and the mixture was stirred at 120-160 rpm for 14-20 hours. After the reaction was completed, the pressure was released, and the mixture naturally cooled to room temperature, and the mixture was washed and filtered with methanol, and then dried in a vacuum oven to obtain the modified sericite powder; The mass ratio of the sericite powder, tetraethyl orthosilicate, triethanolamine and isopropyl alcohol is (5-5.5): (0.8-1): (0.3-0.4): (0.1-0.2); The mass ratio of the pretreated sericite powder, glutaric anhydride and titanate coupling agent is (3-3.4): (1-1.2): (0.15-0.2); The mass ratio of the modified sericite powder, aluminum nitrate, terephthalic acid and acetic acid is (2-2.5): (0.8-1): (1-1.2): (10-15); The average particle size of the sericite powder is 1-2 μm; The antioxidant is any one of antioxidant 1010, antioxidant 168, antioxidant 1076, antioxidant 1098, and antioxidant 1024; The lubricant is at least one of polyethylene wax, polypropylene wax, microcrystalline wax, zinc stearate, calcium stearate, and stearic acid amide; The softener is at least one of white oil, epoxidized soybean oil, naphthenic oil, polyisobutylene, and polyethylene glycol; The crosslinking agent is at least one of maleic anhydride, dimethyl maleate, diethyl maleate, N-phenylmaleimide, N-cyclohexylmaleimide, glycidyl ether type epoxy resin, hexamethylene diisocyanate, and vinyl trimethoxysilane.

2. The hot melt adhesive according to claim 1, characterized in that: The mass ratio of the polyolefin elastomer, the amorphous plastic and the tackifying resin is 7 parts:50 parts:30 parts.

3. The hot melt adhesive according to claim 2, characterized in that: The mass ratio of the amorphous plastic to the modified particles is 50 parts:15.5 parts.

4. The hot melt adhesive according to claim 3, characterized in that: The polyolefin elastomer is an ethylene-α-olefin copolymer.

5. The hot melt adhesive according to claim 4, characterized in that: The amorphous plastic body is an amorphous α-olefin copolymer APAO.

6. The hot melt adhesive according to claim 5, characterized in that: The lubricant is polyethylene wax.

7. The hot melt adhesive according to claim 6, characterized in that: The cross-linking agent includes maleic anhydride and dimethyl maleate; the mass ratio of maleic anhydride to dimethyl maleate is (4.5-5): (1.2-2).

8. The hot melt adhesive according to claim 7, characterized in that: The softener is white oil or epoxidized soybean oil.

9. The hot melt adhesive according to claim 8, characterized in that: The initiator is dicumyl peroxide.

10. A method for preparing the hot melt adhesive according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Mix the tackifying resin, antioxidant, lubricant and softener, heat up to 140-150°C, stir and mix evenly at 100-120rpm to obtain a mixture; S2: Place the mixture in a vacuum high-speed mixer, add polyolefin elastomer and amorphous plasticizer, heat up to 160-180°C, stir and mix at 300-400rpm for 2-2.5h to obtain a hot melt adhesive base; S3: Transfer the hot melt adhesive base to an extruder, add modified particles, a cross-linking agent and an initiator, heat at 140-160°C for 1-1.5h, and then melt-extrude and granulate to obtain the mixture.

Citation Information

Patent Citations

  • EVA adhesive film with high water vapor barrier property

    CN105647406A

  • Flame-retardant hot-melt pressure-sensitive adhesive and preparation method and application thereof

    CN106221629A